Medicinal plants of Borneo - Gibbons, Simon (Professor of medicinal phytochemistry); Teo, Stephen P. (Boca Raton : CRC Press, 2021)
"The rich biodiversity of Borneo provides many useful plants for medicinal uses. Written by experts in the field, Medicinal Plants of Borneo provides a guide and introduction to the medicinal plants from Borneo used traditionally, as well as those plants with medicinal uses from recent discoveries. These include anti-HIV plants - Calophyllum lanigerum (calanolide A) and anti-cancer plant- Aglaia foveolata (silvestrol). It also provides information on the relevant medicinal chemistry, such as bioactive compounds isolated, and the mode of action, where available. This book features relevant photos and illustrations as well as interesting facts that can be found in boxes throughout the text"--
Anti-malarial plants -- Anti-fungal plants -- Anti-mycobacterial plants -- Anti-viral plants -- Anti-cancer plants -- Anti-diabetic plants -- Plants for fever remedy -- Anti-hypertensive plants -- Anti-diarrhoeal plants -- Plants for eye-related diseases -- Plants used in dental treatment -- Plants used as dart poisons -- Plants for arthritis treatment -- Plants used for wound healing.
OCLC-licensed vendor bibliographic record.
Keywords: Materia medica, Vegetable -- Borneo; Medicinal plants -- Borneo; Pharmaceutical chemistry; SCIENCE / Life Sciences / Botany; SCIENCE / Chemistry / General